An Evaluative Study of Nosodes (Advancements in Homeopathic Research, 2020)
It has been noted that Nosodes are poorly reflected in the Repertory, thus calling for an investigation into the subject to find the reasons, if any which can be attempted to overcome by the present practicing Homoeopaths.
Keywords: Homoeopathy; Nosodes; Isopathy; Repertory